FUNCTIONAL ANALYSIS OF FOOD SAFETY AND STANDARDS ACT, 2006, (FSS ACT) IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
The Food Safety and Standards Act, 2006 (FSS Act) is a pivotal legislation in India that plays afundamental role in ensuring the safety and quality of food products for its diverse and populousnation.